Model of Ethical Leadership Based on a System of Relationships in Accordance with Islamic Teachings (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The current study aims to develop a model for ethical leadership based on a system of relationships by Islamic teachings, by presenting the Islamic principles of the concept of leadership as well as the Islamic view of ethics and the components of the system of relationships upon which ethics leadership is based, and which together constitute the Islamic model for ethics leadership.The Researchers followed the descriptive (Content analysis) method of content analysis Due to its possibilities to obtain the largest amount of information available in Islamic literature to help reach conclusions.The Researchers concluded that ethics values are the most prominent player in shaping leadership behavior, and the ethics leader's vision of the relationship system according to the concept set for him and using it correctly and creating a state of balance, harmony, and complementarity among its parts will achieve effectiveness for ethics leadership and dimensions much greater than the leadership vision in other schools.The study concluded with a set of recommendations that can make use of the ethical leadership model in practice The most important ones : The need for extensive studies of the topic of moral leadership in the Islamic literature and spread ethical concepts at all organizational levels as well as the level of senior leadership As well as the emphasis on making moral values a criterion for evaluation within organizations